1995
DOI: 10.1002/pdi.1960120409
|View full text |Cite
|
Sign up to set email alerts
|

Does the time of diagnosis of Type 2 diabetes have a seasonal variation?

Abstract: This prospective, observational study from 1987 to 1990 inclusive, set in hospital diabetes clinics in Leicester City, England (population 287,000), sought to establish whether or not Type 2 diabetes has a seasonal variation in incidence. The dates of diagnosis of 833 newly diagnosed Type 2 diabetic patients were recorded and total monthly incidence over the four year period calculated. Seasonal incidence was assessed by the Edward's test and the test for uniformity on a circle. No seasonal variation in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…All 41 studies included in the epidemiological analysis were published between 1991 30 and 2020 31,32 . The included studies reported data from 12 different countries, with the number of papers from each country as follows: Austria—2, 33,34 Denmark—4, 32,35–37 France—4, 31,36–38 Finland—1, 39 Germany—9, 8,38,40–46 Hungary—1, 47 Belgium—1, 38 Italy—4, 38,48–50 the Netherlands—2, 38,51 Spain—3, 38,52,53 Sweden—5, 30,38,54–56 and United Kingdom—14 38,57–69 (Figure 2). Some papers reported data on more than one country.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All 41 studies included in the epidemiological analysis were published between 1991 30 and 2020 31,32 . The included studies reported data from 12 different countries, with the number of papers from each country as follows: Austria—2, 33,34 Denmark—4, 32,35–37 France—4, 31,36–38 Finland—1, 39 Germany—9, 8,38,40–46 Hungary—1, 47 Belgium—1, 38 Italy—4, 38,48–50 the Netherlands—2, 38,51 Spain—3, 38,52,53 Sweden—5, 30,38,54–56 and United Kingdom—14 38,57–69 (Figure 2). Some papers reported data on more than one country.…”
Section: Resultsmentioning
confidence: 99%
“…The data source from which each study retrieved epidemiological data was highly heterogeneous within the publications, and most of the data were collected in databases, previous studies, or clinical/laboratory settings. A few examples of settings and databases cited in the papers were as follows: Hospitals, 35,52,56,69 social security systems, 43 primary care centers, 52,55 clinical centers/practices, 49,56,57,59,66 health information network, 44,68 laboratories, 35,50 national health systems, 31,32,34,35,49 health insurance systems, 8,39,46,47,56 surveys, 30,44 and research datalinks 33,38,39,48,54,58,60,61,63,65,67 . Secondary data analysis based on the following databases was published: AOK, 41 CPRD, 61,65,67 RECAP‐DM, 55 SHIP, 44 EMIS, 68 CARLA, 44,45 DHS, 44 HNR, 44 KORA, 40,44 EPIC, 57,64 Ely, 59,62 Inter99, 36,37 D.E.S.I.R, 36,37 ACG, 48 Asturias, 53 ZODIAC, 51 BPSU, 58 and CODE‐2 38 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations